Effect of Plant Density on the Physiological and Quality Trait for Different Varieties of Wheat (Triticum aesitivum L.) - Mohammed Khursheed; Zhala Muhammad Ameen (Al-Qadisiyah Journal For Agriculture Sciences, 2023)
A factorial experiment was carried out in the experimental field of the Ankawa Research Center in Erbil Governorate, during the spring season of 2023 to know the effect of plant density on the morphological characteristics of different varieties of wheat. The randomized complete block design (RCBD) was used with three replicates, where three varieties of wheat were planted: Adana99, Hawler2, Hawler4, and three levels of plant or seed densities (450, 400, 350) m2. The results showed significant differences between the average interference of plant density with wheat varieties for the studied characteristics, as the average overlap between the density exceeded (400) plants. m2 and the Hawler2 variety in terms of significance and in terms of being the highest values of the averages in all the characteristics studied over the rest of the average overlap between densities and varieties. Returning to the average interaction between the density (400) plants. m2 and class Hawler2 The average overlap values were (11.36) for chlorophyll content (A), (3.23) for chlorophyll content (B), (5.22) for carotene content, (206.05) for protein content in dry leaves and stems, (205.08) for proline content in leaves, (4.24) for ascorbic acid content, (42.77) for soluble sugars content, (80.73) for carbohydrate content, (4.99) for phosphorus percentage, and (36.15) for nitrogen percentage. And (15.61) for the percentage of potassium, (10.16) for the percentage of calcium, and (3.26) for the percentage of magnesium.